2020
DOI: 10.1111/sltb.12622
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Mediates the Association between Disclosure of Suicide Attempt and Depression, Perceived Burdensomeness, and Thwarted Belongingness

Abstract: Objective Prior research has found disclosure of concealable stigmatized statuses, including suicide attempt survivorship, to be associated with positive mental health outcomes. This study sought to test the mediating effect of self‐reported social support on the association between disclosure of suicide attempt and suicide risk factors in a sample of undergraduate college students. Method Data were analyzed from 149 undergraduate college students with a history of one or more suicide attempts. Three parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Although the coping processes were associated with a greater caregiver regard for the Veteran (as rated by both respondents), cross-partner effects suggested that Veterans' social coping was associated with higher time demands on caregivers. While broadly consistent with previous work on how disclosure elicits support (McClay et al, 2020), it also highlights the practical demands on the caregiver. Alternatively, it might suggest that high levels of caregiver time investment encourage the Veteran to lean on family relationships more.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Although the coping processes were associated with a greater caregiver regard for the Veteran (as rated by both respondents), cross-partner effects suggested that Veterans' social coping was associated with higher time demands on caregivers. While broadly consistent with previous work on how disclosure elicits support (McClay et al, 2020), it also highlights the practical demands on the caregiver. Alternatively, it might suggest that high levels of caregiver time investment encourage the Veteran to lean on family relationships more.…”
Section: Discussionsupporting
confidence: 82%
“…The present study examines the interplay of these risk and protective factors in a truly interpersonal context. Our findings conceptually extend prior links between disclosure of suicide (a component of external suicide-related coping), thwarted belongingness, perceived burdensomeness, and family reactions (Frey & Fulginiti, 2017;McClay et al, 2020). However, a greater degree of complexity emerges once these links are placed into the context of larger caregiver experiences, emphasizing the importance of attending to the family unit when caring for Veterans with a history of STB.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…It has already been demonstrated that TB is positively associated with depression [12] and social anxiety [13], as well as fear of negative evaluation [14], negative interpersonal trust [15], insomnia [16][17][18], and perceived illness stigma in youth with inflammatory bowel disease [19]. Further, it could be shown that TB is inversely related to involvement in extracurricular activities in young adults [20], social support resulting from the disclosure of a suicide attempt from students with a history of suicide attempts [21], and the existence of a partnership in gay men [22]. Moreover, mixed findings are already available for newer technologies, illustrating that the influence of online interactions on TB is still unclear.…”
Section: Introductionmentioning
confidence: 99%